Selecting squash (Cucurbita sp.) introductions by seed nutritional quality and seed meal (2019)
Squash (Cucurbita sp.) is widely used in Colombia as both food and animal feed. However, its seeds are discarded. This study  aimed to identify squash genotypes with a high nutritional value in the whole seed meal (WSM) and defatted seed meal (DSM) within a group of 19 introductions (14 of Cucurbita moschata and 5 of C. sororia). For WSM, 70% of the introductions presented above-average values for extract (36.9%) and crude protein (26.34%); the fiber values were 20.34% neutral detergent fiber (NDF) and 13% acid detergent fiber (ADF). For DSM, 57% of the introductions presented above-average crude protein (43.5%) and 52% above-average crude energy values (4078 cal g-1).  Based on the relative feed value (RFV), introductions 1229, 1200, 1201, 1219 and 1206 were selected for WSM, and 1206 1229, 932, 1200, 786 and 954 were selected for DSM. In the selected C. moschata introductions, parents with general and specific combining abilities for ether extract and crude protein in WSM or high RFV in DSM should be identified. C. soraria introductions 1202 and 954 should be used in crosses that aim to obtain F2 segregants for seeds with a high oil content and high RFV in DSM.